2016
DOI: 10.4025/actascihealthsci.v38i2.29409
|View full text |Cite
|
Sign up to set email alerts
|

<b>Evaluation of <i>Staphylococcus aureus</i> resistance profile isolated from nursing students in an institution of higher education

Abstract: Staphylococcus aureus causes a large variety of infections, where many of them are acquired in the hospital environment. A significant part of the population is a nasal carrier of this type of microorganism. The present study evaluated the nasal colonization by S. aureus, identifying its resistance profile in nursing students from a private educational institute of higher education. Nasal swab samples were collected and identified for S. aureus. Moreover, an antibiogram assay was performed, followed by the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
0
1
Order By: Relevance
“…In the present study, 18.34% of the S. aureus-positive samples were resistant to erythromycin and cefoxitin and 11.67% were resistant to oxacillin. These findings are not consistent with a previous study of nasal carriers of S. aureus in nursing students that reported the rate of S. aureus positivity as 32.5%, MRSA as 10%, and resistance to erythromycin as 30% (20). According to our results, 6.67% of the isolates were resistant to clindamycin that contradicts the findings of da Silva et al in Pernambuco; they assessed resistance to clindamycin among nursing staff in a teaching hospital and reported that 11.9% of the nasal carriers were resistant to clindamycin (21).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, 18.34% of the S. aureus-positive samples were resistant to erythromycin and cefoxitin and 11.67% were resistant to oxacillin. These findings are not consistent with a previous study of nasal carriers of S. aureus in nursing students that reported the rate of S. aureus positivity as 32.5%, MRSA as 10%, and resistance to erythromycin as 30% (20). According to our results, 6.67% of the isolates were resistant to clindamycin that contradicts the findings of da Silva et al in Pernambuco; they assessed resistance to clindamycin among nursing staff in a teaching hospital and reported that 11.9% of the nasal carriers were resistant to clindamycin (21).…”
Section: Discussioncontrasting
confidence: 99%